Advancing Nanotechnology: Targeting Biofilm-Forming Bacteria with Antimicrobial Peptides - Campos, Julia Valladares [UNESP]; de Pontes, Janaína Teixeira Costa [UNESP]; Canales, Christian Shleider Carnero; Roque-Borda, Cesar Augusto; Pavan, Fernando Rogério [UNESP] (My University, 2025)
Nanotechnology offers innovative solutions for addressing the challenges posed by biofilm-forming bacteria, which are highly resistant to conventional antimicrobial therapies. This review explores the integration of pharmaceutical nanotechnology with antimicrobial peptides (AMPs) to enhance the treatment of biofilm-related infections. The use of various nanoparticle systems—including inorganic/metallic, polymeric, lipid-based, and dendrimer nanostructures—provides promising avenues for improving drug delivery, targeting, and biofilm disruption. These nanocarriers facilitate the penetration of biofilms, down-regulate biofilm-associated genes, such as ALS1, ALS3, EFG1, and HWP1, and inhibit bacterial defense mechanisms through membrane disruption, reactive oxygen species generation, and intracellular targeting. Furthermore, nanoparticle formulations such as NZ2114-NPs demonstrate enhanced efficacy by reducing biofilm bacterial counts by several orders of magnitude. This review highlights the potential of combining nanotechnology with AMPs to create novel, targeted therapeutic approaches for combatting biofilm-related infections and overcoming the limitations of traditional antimicrobial treatments.